The Osseous Pathology of Purpura Fulminans in a Two- Year-Old Child: A Case Report - Mohd-Razali S; Ahmad-Affandi K; Ibrahim S; Abdul-Rashid AH; Abdul-Shukor N (Malaysian Orthopaedic Journal, 2023)
Purpura fulminans (PF) is a severe clinical manifestation of Neisseria meningitides infection that is associated with high mortality rates in children. Survivors are frequently left with debilitating musculoskeletal sequelae. There is a paucity of reports on the musculoskeletal pathology of purpura fulminans. We report on a 2-year-old boy with purpura fulminans due to meningococcemia. The child developed distal gangrene in both the upper and lower limbs. Amputations were done for both lower limbs. Histological examination of the amputated specimens showed an inflammatory process and features of osteonecrosis. The latest follow-up at the age of 6 years showed a right knee valgus due to asymmetrical growth arrest of the proximal tibia. PF and its complications are challenging to treat and may require a multidisciplinary approach to improve patient’s functional ability.